Detection of Thyroid Papillary Carcinoma Lymph Node Metastases Using One Step Nucleic Acid Amplification (OSNA): Preliminary Results. (1st June 2015) - González, Oscar; Iglesias, Carmela; Zafon, Carles; Castellví, Josep; García-Burillo, Amparo; Temprana, Jordi; Caubet, Enric; Vilallonga, Ramón; Mesa, Jordi; Cajal, Santiago Ramón y; Fort, José Manuel; Armengol, Manel; et al.
ABSTRACT Purpouse: One Step Nucleic Acid Amplification (OSNA) has been previously proposed for the diagnosis of lymph node metastases (LNMs) from several malignant conditions by quantifying the number of copies of cytokeratin 19 mRNA. Our aim was to evaluate the results obtained by OSNA in the lymph nodes of patients with papillary thyroid carcinoma (PTC) by comparing our results with the findings observed using standard pathological examination. Materials and Methods: Fifty human lymph nodes (from five patients with diagnosed PTC) were studied. Each node was divided into two: one half was used for molecular study ("OSNA-node"), and the other half was used for conventional staining with hematoxylin and eosin ("HE-non-OSNA node"). Three cytological imprints using Papanicolaou and May-Grunwald-Giemsa strains were obtained from both node halves. The results from each technique were compared, and ROC analysis was performed. Results: The OSNA study showed 22 positive samples for LNM (44%), which demonstrate a high concordance rate with the results observed using conventional pathological examination (cytology of "OSNA-node" and HE of "Non-OSNA node") with specificity and sensitivity values greater than 86% and 89%, respectively. However, both comparisons differed in the number of copies of mRNA as the best cut-off (260 copies in the first case and 93 in the second case). Conclusions: The OSNA results for the detection of LNM in patients with PTC are comparable with those observed using conventional techniques. However, its quantitative nature could be useful to more accurately detect lymph node involvement.